A tale of four parsers: methodological reflections on diagnostic evaluation and in-depth error analysis for meaning representation parsing. - Buljan, Maja; Nivre, Joakim; Oepen, Stephan; Øvrelid, Lilja (Language Resources & Evaluation, 2022)
We discuss methodological choices in diagnostic evaluation and error analysis in meaning representation parsing (MRP), i.e. mapping from natural language utterances to graph-based encodings of semantic structure. We expand on a pilot quantitative study in contrastive diagnostic evaluation, inspired by earlier work in syntactic dependency parsing, and propose a novel methodology for qualitative error analysis. This two-pronged study is performed using a selection of submissions, data, and evaluation tools featured in the 2019 shared task on MRP. Our aim is to devise methods for identifying strengths and weaknesses in different broad families of parsing techniques, as well as investigating the relations between specific parsing approaches, different meaning representation frameworks, and individual linguistic phenomena—by identifying and comparing common error patterns. Our preliminary empirical results suggest that the proposed methodologies can be meaningfully applied to parsing into graph-structured target representations, as a side-effect uncovering hitherto unknown properties of the different systems that can inform future development and cross-fertilization across approaches.